PENGEMBANGAN BAHAN AJAR BERBASIS PEMBELAJARAN BERDIFERENSIASI MATERI "KEBERAGAMAN BUDAYA INDONESIAKU” KELAS V MI T BERKAH PALANGKARAYA - Muhammad Syabrina; Fadilla Dhea Alfira; Syawfia Anggeraini; Vindo Lafayza (JURNAL ILMIAH NUSANTARA, 2026)
This study aims to develop differentiated learning-based teaching materials on the topic “Keberagaman Budaya Indonesiaku” for fifth grade students at MI Terpadu Berkah Palangkaraya. The research employed the Research and Development (R&D) method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. Data collection techniques included interviews, observations, documentation, questionnaires, and learning outcome tests. The developed product was validated by material experts and design experts, followed by teacher assessments and field trials involving 13 students. The validation results showed that the teaching materials were categorized as highly feasible, with a score of 96.90% from material experts, 90.70% from design experts, 94.10% from teacher assessments, and 89.60% from field trials. The effectiveness test using the paired sample T-test indicated a significant difference between pretest and posttest results with a significance value of 0.01. Furthermore, the N-Gain test obtained an average score of 0.57, categorized as moderate improvement, while the effectiveness percentage reached 57.14% with a fairly effective category. Therefore, the differentiated learning-based teaching materials developed are considered feasible and effective in improving students’ learning outcomes and supporting more engaging learning activities.